The asset portfolios of native-born and foreign-born households - Deborah A. Cobb-Clark; Vincent A. Hildebrand (Institute for the Study of Labor (IZA), 2008)
This paper analyses the net worth and asset portfolios of native- and foreign-born Australian families using HILDA (wave 2) data. Specifically, we estimate a system of asset equations with an adding-up constraint imposed to control for variation in households' total net worth. Our results indicate that after accounting for differences in human capital and income levels, single immigrants have a wealth advantage of almost 185,000 relative to single native-born individuals. Although the wealth gap between mixed and native-born couples is not statistically significant, immigrant-only couples have approximately 150,000 less wealth on average than native-born couples. Relative to equally wealthy native-born couples, immigrant-only couples hold substantially more of their wealth in their homes and less in the form of vehicles and financial assets. Mixed couples, on the other hand, allocate their wealth across assets in the same way as native-born couples.
Keywords: J61; 330; Wealth; immigrants; housing; Vermögensverteilung; Migranten; Australien